The Left Superior Longitudinal Fasciculus within the Primary Sensory Area of Inferior Parietal Lobe Plays a Role in Dysgraphia of Kana Omission within Sentences - Nobusada Shinoura; Akira Midorikawa; Toshiyuki Onodera; Ryozi Yamada; Yusuke Tabei; Yasumitsu Onda; Chihiro Itoi; Seiko Saito; Kazuo Yagi (Behavioural Neurology)
Functional neurological changes after surgery combined with diffusion tensor imaging (DTI) tractography can directly provide evidence of anatomical localization of brain function. Using these techniques, a patient with dysgraphia before surgery was analyzed at our hospital in 2011. The patient showed omission of kana within sentences before surgery, which improved after surgery. The brain tumor was relatively small and was located within the primary sensory area (S1) of the inferior parietal lobe (IPL). DTI tractography before surgery revealed compression of the branch of the superior longitudinal fasciculus (SLF) by the brain tumor. These results suggest that the left SLF within the S1 of IPL plays a role in the development of dysgraphia of kana omission within sentences.